Cholestan Steroids from The Stem Bark of Aglaia angustifolia Miq and Their Cytotoxic Activity against MCF-7 Breast Cancer Cell Lines - Hutagaol, Ricson Pemimpin; Mozef, Tjandrawati; Fajriah, Sofa; Primahana, Gian; Supratman, Unang; Harneti, Desi; Hidayat, Ace Tatang; Awang, Khalijah; Shiono, Yoshihito (Molekul, 2023)
With about 120 species, Aglaia is one of the largest genera of the plant family Meliaceae (the mahogany plants). Various Aglaia species have been investigated since the 1960s for their phytochemical constituents and biological properties. This research objective was to find secondary metabolites that have activity as anti-breast cancer compounds from endemic Indonesian Aglaia, such as Aglaia angustifolia Miq. Two cholestan type steroids, stigmast-5en-3α-acetat (1), as a new steroid with α-sterochemistry of acetyl moiety at C-3 and 23a-homostigmast-5en-3β-ol (2), with unusual side chain were isolated for the first time from the stem bark of Aglaia angustifolia Miq or known as segara tree in Kalimantan. The chemical structures of two steroids were identified with spectroscopic data, including IR, NMR (1H, 13C, DEPT 135°, HMQC, HMBC, NOESY, 1H-1H COSY) and HRTOF-MS, as well as by comparing with previously reported spectral data. These two steroids were isolated for the first time from this genus. Steroids 1 and 2 were evaluated for cytotoxic activity against MCF-7 breast cancer cells and showed weak activity with IC50 values of 829.0 and 903.0 µg/mL, respectively.